Densification of Bi0.5Na0.5ZrO3 ceramic using liquid-phase sintering method - Jaiban P. (2014)
Lead-free bismuth sodium zirconate (BNZ) ceramics with formula Na 0.5Bi0.5ZrO3/xBi2O3 with x = 0, 2, 3, 4, and 6 wt% were prepared by liquid-phase sintering method. The specimens were sintered at 850 and 900 °C. Phase identification was investigated using X-ray diffraction technique. BNZ/4 wt% Bi2O3 and BNZ/6 wt% Bi2O 3 ceramics sintered at 900 °C showed impurity phase of Bi 7.38Zr0.62O12.31 compound due to excess additive reacted with zirconium in system. Scanning electron microscopy and energy-dispersive X-ray spectroscopy were employed to study microstructure and measure chemical composition of ceramics, respectively. The results revealed creation of bismuth oxide liquid phase at BNZ grain boundaries inhibited grain growth and decreased pore size. This caused the relative densities of the modified samples to increase.